A cooperative game theory analysis for transmission loss allocation - Lima, Delberis A. [UNESP]; Contreras, Javier; Padilha-Feltrin, Antonio [UNESP] (Elsevier B.V. Sa, 2008)
This paper presents an analysis and discussion, based on cooperative game theory, for the allocation of the cost of losses to generators and demands in transmission systems. We construct a cooperative game theory model in which the players are represented by equivalent bilateral exchanges and we search for a unique loss allocation solution, the Core. Other solution concepts, such as the Shapley Value, the Bilateral Shapley Value and the Kernel are also explored. Our main objective is to illustrate why is not possible to find an optimal solution for allocating the cost of losses to the users of a network. Results and relevant conclusions are presented for a 4-bus system and a 14-bus system. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: loss allocation; equivalent bilateral exchanges; Core; Shapley Value; Bilateral Shapley Value; Kernel